Community perception on factors that contribute to illegal logging and land encroachment in Kampung Jelawang, Kelantan - Kamal, Nur Aqilah (2019)
Despite the systemic problems associated with illegal logging in Kelantan, minimal research has been taken to explore the reasons underlying these practices particularly in small region within the state. This study was conducted in Kampung Jelawang, Kelantan and the objectives were to determine the factors that contribute to illegal logging and land encroachment. A total of 104 respondents were interviewed through questionnaire survey. The information about socio-economic background, such as gender, age, race, education level, occupation and income were collected. The data were analysed using SPSS software to obtain descriptive data and correlation analysis. This study identified the underlying major factor for both illegal logging and land encroachment in Kampung Jelawang are weak law enforcement. The correlation analysis revealed that the relationship between the awareness of illegal logging activities in the studied area with respondent’s age is positively but weakly correlated. This study also showed that the relationship between deforestation has an impact on flood risk with education level resulted have a weak negative relationship. Therefore, the related department should give more attention to strengthen the forest policy and enforcement division in minimizing the occurrence of illegal activities in forest sector.